Waist-to-Height Ratio (WHtR) in Predicting Coronary Artery Disease Compared to Body Mass Index and Waist Circumference in a Single Center from Saudi Arabia - Mostafa Q. Alshamiri; Faisal Mohd A Habbab; Saad Saeed AL-Qahtani; Khalil Abdullah Alghalayini; Omar Mohammed Al-Qattan; Fayez El-shaer (Cardiology Research and Practice)
This study aims to study the efficiency of the Waist-to-Height Ratio (WHtR) for determining coronary artery disease. It compares the frequency of abnormal WHtR, as a proxy for abdominal obesity, to that of body mass index (BMI) and waist circumference (WC). It also relates the findings to other cardiometabolic risk factors in University Hospital patients. A cross-sectional study design was used, where a sample of 200 patients (142 males and 58 females) who attended the adult cardiac clinic were purposively included. BMI, WC, and WHtR were measured, where frequencies of WHtR were compared to those of BMI and WC. The findings were related to the history of coronary artery disease (CAD) and history of cardiometabolic risk factors, including diabetes mellitus (DM), hypertension (HTN), and hyperlipidemia. Majority of the male patients were older, taller, and had a lower BMI value. It also showed that the prevalence of dyslipidemia and CAD was higher in male patients. No significant difference between both genders was noticed for weight, WC, WHtR, hypertension, or DM. BMI was least associated with high-risk cardiac population in both males and females (39.4% and 60.3%), followed by WC (84.5% and 96.6%, respectively). WHtR showed the highest association with gender (male 98.6% and females 98.3%). These findings were noticed in patients with all risk factors. WHtR is superior to BMI and WC for determining the elevated risk of diabetes, hypertension, dyslipidemia, and CAD in a single university institute. The role of WHtR in both normal and diseased Saudi population should be delineated.